INTERPRETASI POLA SEBARAN INDIKASI MUDVOLCANO DI SURYANATA SAMARINDA DENGAN METODE GEOLISTRIK KONFIGURASI WENNER-SCHLUMBERGER - Wiranata, Doni; Natalisanto, Adrianus Inu (GEOSAINS KUTAI BASIN, 2018)
This research was conducted to know the indication of mud volcano distribution pattern using geoelectric method. This research began with geological mapping along the geoelectric path and then retrieved the data using the Wenner-Schlumberger configuration. Then the field data was processed using Res2dinv software to display cross section of each path. Interpretation of the presence of mudvolcano was indicated by resistivity value (4.5 ± 0.5) Ωm and chargeability value (60 ± 20) msec. The existence of mudvolcano was supported by the presence of bursts.mudvolcano, geoelectric method, Chargeability, Resistivity